Using archival versions of apps to understand emerging digital ecosystems. - Burroughs, James; Mathew, Ashwin; Oreglia, Elisa (Big Data & Society, 2025)
Archival versions of apps present a unique opportunity to study how apps functioned at different points in time, how they evolved individually, and how their roles in wider digital ecosystems can be useful to understand the increasing dominance of platforms as organizers of the internet. In this paper, we propose a novel approach to studying apps' histories by analysing the URLs embedded in their code, and a tool, Janus, to automate the collection and analysis of apps, and output visualisations of their hard-coded links. By pruning these URLs at different levels, these visualisations can show an app's map of connectivity at various levels of detail (domain, subdomain and full URL) across time. We propose Janus as a locus of multidisciplinary research, to triangulate findings especially from qualitative researchers, but also to identify new lines of inquiry for different disciplines. We test Janus and its potential for multidisciplinary research on historical versions of the Kazakhstani 'super-app' Kaspi and of other local financial apps.